The Impact of Cross-Cultural Adaptation on the Psychology and Entrepreneurial Intention of Venture Entrepreneurs - Ye, Long; Dong, Xu-Yang (Frontiers in Psychology, 2021)
The purpose is to integrate cultural psychology into cross-cultural adaptation and analyze the factors of entrepreneurial psychology and entrepreneurial intention of venture entrepreneurs. The research framework of cross-cultural adaptation is constructed, and four hypotheses are put forward, and 100 venture entrepreneurs in multinational enterprises are randomly recruited and investigated through the QS (Questionnaire Survey) design. Finally, the results are analyzed through statistical software. The results show that among the basic information of venture entrepreneurs, the proportion of gender is balanced, and the educational level is generally high, with the majority of young entrepreneurs aged 20 – 35. Meanwhile, there are significant differences in the four dimensions of cross-cultural competence, cross-cultural adaptation, entrepreneurial intention, and psychological adaptation of venture entrepreneurs (p<0.05). Length of service influences cross-cultural competence, cross-cultural adaptation, and entrepreneurial intention but doesn’t affect psychological adaptation. Hence, cross-cultural adaptation has a great impact on the entrepreneurial intention and psychological adaptation of venture entrepreneurs and provides a practical basis for the entrepreneurial optimization of venture entrepreneurs.